Optimised method for the analysis of phenolic compounds from caper (Capparis spinosa L.) berries and monitoring of their changes during fermentation. (1st April 2016) - Francesca, Nicola; Barbera, Marcella; Martorana, Alessandra; Saiano, Filippo; Gaglio, Raimondo; Aponte, Maria; Moschetti, Giancarlo; Settanni, Luca
Highlights: A method to identify and quantify polyphenols from caper berries was developed. HPLC–ESI–MS method successfully identified 9 polyphenols. Epicatechin was found in untreated fruits, quercetin in processed caper berries. Lactobacillus pentosus dominated among the microbial communities during fermentation. The addiction of starter culture reduced the bitter taste of fermented caper berries. Abstract: In this work, an ad hoc method to identify and quantify polyphenols from caper berries was developed on high-performance liquid chromatography/electrospray ionisation source/mass spectrometry (HPLC–ESI–MS). The method was applied during fermentation carried out with Lactobacillus pentosus OM13 (Trial S) and without starter (Trial C). A total of five polyphenols were identified. All samples contained high concentrations of rutin. Epicatechin was found in untreated fruits, on the contrary quercetin was detected during fermentation. Trial S was characterised by a more rapid acidification and lower levels of spoilage microorganisms than Trial C. L. pentosus dominated among the microbial community of both trials and the highest biodiversity, in terms of strains, was displayed by Trial C. Aureobasidium pullulans was the only yeast species found. The analytical method proposed allowed a high polyphenolic compound recovery from untreated and processed caper berries in short time. The starter culture reduced the bitter taste of the final product.